Eating disorder recovery in men: A pilot study. Issue 12 (16th August 2019) - Bardone‐Cone, Anna M.; Johnson, Shelby; Raney, Thomas J.; Zucker, Nancy; Watson, Hunna J.; Bulik, Cynthia M.
Abstract: Objective: This pilot study examined the validity of a comprehensive definition of recovery (physical, behavioral, and cognitive recovery indices) for the first time in men. Method: Men with an eating disorder history were recruited from former patients at eating disorder centers, university campuses, and fitness centers/gyms. At baseline and a 12‐month follow‐up, data were collected via online surveys, diagnostic interviews, and measured weight and height from men with an eating disorder history ( n = 36) and men with no eating disorder history ( n = 27). Results: Of the men with an eating disorder history, 15 met criteria for an eating disorder, 7 met criteria for partial recovery, and 5 for full recovery. Men who met criteria for full recovery did not differ significantly from men with no eating disorder history and had significantly lower levels of broad eating pathology, thinness and restricting expectancies, body shame, difficulties in stopping thoughts about body, food, or exercise, and male body attitudes related to muscularity and body fat than men with an eating disorder. Men meeting criteria for full recovery had higher levels of body acceptance and intuitive eating than men who met criteria for partial recovery or an eating disorder. In terms of predictive validity, of those fully recovered at baseline, 60% also met full recovery criteria at follow‐up. Discussion: Preliminary findings suggest that a comprehensive definition of recovery applies to men. Although research with larger samples is needed, this research provides some optimism for the potential of recovery in men.